Agro business in a changing competitive environment – Campania firms' strategic, marketing and financial choices. (1st January 2014) - Rossi, Matteo; Vrontis, Demetris; Thrassou, Alkis
Over the last few years, the agro food industry has been undergoing a process of accelerated change. This exploratory research analyses the strategic choices of Campania (Italy) agro food firms and focuses on competitive issues; issues that are largely affected by the mono-product nature of the SMEs, which characterise the economy of Campania. In this context, the paper investigates the critical factors of success and/or failure of the Campania agro food industry, the strategies adopted by firms, their resulting performance, their capital structure and the actions necessary to increase competitiveness. The methodology is based on secondary data research, literature review, and a survey of 97 firms and 12 experts' interviews. The research demonstrates some strategic problems of Campania firms, relating to competition, decision making and financial performance. Some firms were found to implement winning strategies, with their most important characteristic being their marketing orientation.